Transforming Teaching and Learning Through Critical Media Literacy Pedagogy (LEARNing Landscapes, 2013)
This article provides a framework and examples for critical media literacy pedagogy. More than simply guiding how students read and interpret the texts they encounter, critical media literacy pedagogy pushes to illuminate the underlying power structures that are a part of every media text. Throughout this article, examples from working with high school youth and preservice teachers are provided. In recognizing recent shifts in media production as a result of participatory culture, this article focuses on how youth-created media products are an integral part of a 21st century critical media literacy pedagogy.
Keywords: media literacy; critical; pedagogy; youth; preservice teacher; participatory culture; teaching; learning; power structures; youth created media